2023
DOI: 10.1039/d2mh01226j
|View full text |Cite
|
Sign up to set email alerts
|

Large-area 2D bismuth antimonide with enhanced thermoelectric properties via multiscale electron–phonon decoupling

Abstract: It is a challenge to obtain high thermoelectric efficiency, owing to the conflicting parameters of the materials that are required. In this work, the composition-adjustable 2D bismuth antimonide (Bi100-xSbx) is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…This is in agreement with Olijnyk et al [56] and Höhne et al [61], who worked on bulk Bi and found a rather similar FWHM, but in contrast with the results of Lu et al who worked on thin film of Bi [62]. We found that the FWHM of the E g mode did not change significantly with Sb alloying, as also found by Zhao et al in the case of 2D layers of Bi 1−x Sb x for x ≤ 0.15 [58]. This was also the case for bulk Bi 0.9 Sb 0.1 compared to the Bi reference in Lannin's work [55] if we examine their Raman spectra in detail.…”
Section: Raman Scatteringsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in agreement with Olijnyk et al [56] and Höhne et al [61], who worked on bulk Bi and found a rather similar FWHM, but in contrast with the results of Lu et al who worked on thin film of Bi [62]. We found that the FWHM of the E g mode did not change significantly with Sb alloying, as also found by Zhao et al in the case of 2D layers of Bi 1−x Sb x for x ≤ 0.15 [58]. This was also the case for bulk Bi 0.9 Sb 0.1 compared to the Bi reference in Lannin's work [55] if we examine their Raman spectra in detail.…”
Section: Raman Scatteringsupporting
confidence: 92%
“…In the more recent works, Sultana et al also observed only additional peaks at about 120 cm −1 and 140 cm −1 [55], whereas Zhao et al observed only these peaks for x ≤ 0.18 and all the five peaks only for x ≥ 0.27 [56], and Lee et al observed only one weak additional peak at about 118 cm −1 in their sample with x =0.04 [60]. In contrast, in our samples, we observed the peak at around 110 cm −1 even for low Sb content, and it is located at lower frequencies than in single-crystalline samples [54,55] and the same frequency as in the 2D layer of Bi 0.65 Sb 0.35 studied by Zhao et al [58]. These differences are probably due to the small grain size and/or disordering in our samples.…”
Section: Raman Scatteringcontrasting
confidence: 85%
See 2 more Smart Citations